STRATEGI PENGEMBANGAN KAWASAN AGROPOLITAN RURUKAN KOTA TOMOHON (Development Strategy of Rurukan Agropolitan Area, Tomohon City) - Juan Joshua Wokas; Melsje Y. Memah; Jenny Baroleh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aims to describe the characteristics of Rurukan Agropolitan Area and designing development strategies of Rurukan Agropolitan Area. The datas used in this study are primary datas obtained from FGD with 13 respondents consists of parties that related with this study using questionnaire, and secondary datas obtained from agencies, literatures, and previous researches that are related to this study. The results showed that, Rurukan Agropolitan Area had adequate natural resources, facilities and huge potentials to develop as Agropolitan Area. The result of SWOT analysis diagram showed that Development of Rurukan Agropolitan Area is in the first quadrant, means is in favourable position, strengths and opportunities for further development. Keywords: Regional development, Agropolitan